2016
DOI: 10.1186/s12864-016-3008-4
|View full text |Cite
|
Sign up to set email alerts
|

Antennal transcriptome analysis and expression profiles of odorant binding proteins in Eogystia hippophaecolus (Lepidoptera: Cossidae)

Abstract: BackgroundEogystia hippophaecolus (Hua et al.) (Lepidoptera: Cossidae) is the major threat to seabuckthorn plantations in China. Specific and highly efficient artificial sex pheromone traps was developed and used to control it. However, the molecular basis for the pheromone recognition is not known. So we established the antennal transcriptome of E. hippophaecolus and characterized the expression profiles of odorant binding proteins. These results establish and improve the basis knowledge of the olfactory rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 87 publications
(85 reference statements)
6
20
0
Order By: Relevance
“…A t-test was performed for the qPCR data. β-Actin was used as the reference gene to normalize target gene expression [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…A t-test was performed for the qPCR data. β-Actin was used as the reference gene to normalize target gene expression [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Specific primers (supplementary material 1) for qRT-PCR were designed based on the sequences of ORFs using Primer Premier 5.0 [45]. The E. hippophaecola actin gene was used as a reference [40,41,46] and we used Bestkeeper to evaluate the std value (<1) of actin gene under different temperatures which indicated that actin gene was stable [47]. The qRT-PCR was carried out on a Bio-Rad CFX96 PCR machine (Hercules, CA) in a reaction mixture of 12. in three biological replicates, and each sample was technically repeated three times.…”
Section: Expression Of Ehhsp90 Under Different Treatmentsmentioning
confidence: 99%
“…OBPs are soluble proteins with low molecular weights and are mainly expressed in the lymph of antenna sensilla [28][29]. Some OBPs exhibit specific binding with hydrophobic odorant molecules and can deliver the molecules to membrane-binding receptors [30][31][32][33]. Typical OBPs have six conserved cysteine residues, which form three pairs of disulfide bridges [28][29][34][35].…”
Section: Introductionmentioning
confidence: 99%